Rastreamento e longitudinalidade do cuidado ofertado ao usuário com hipertensão arterial sistêmica e/ou diabetes mellitus: ações adotadas por profissionais da Atenção Primária à Saúde da Paraíba - Guimarães, Dayverson Luan de Araujo (2025)
Introduction: Non-communicable chronic diseases (NCDs) represent the leading cause of premature death worldwide, placing a heavy burden on health systems, especially in developing countries. Hypertension (HTN) and Diabetes Mellitus (DM) are particularly prominent in the national context, and the state of Paraíba is no exception, given their high prevalence, harmful consequences for individuals’ health, and high costs for the Unified Health System (SUS), which must structure its actions with Primary Health Care (PHC) as the coordinator and organizer of care. Objective: To describe the screening and continuity-of-care actions provided by primary health care professionals in the state of Paraíba to users with systemic arterial hypertension and/or diabetes mellitus. Methodology: This is a cross-sectional descriptive study. Data collection occurred between December 2022 and April 2023. Sampling was defined by selecting, within each of the state’s 16 health regions, the municipality with the highest prevalence of overweight/obesity, considering the typology criteria proposed by the IBGE. The final sample comprised eight urban municipalities, five adjacent intermediate municipalities, and 14 adjacent rural municipalities, totaling 27 municipalities. One health professional from each Basic Family Health Unit (excluding anchor units) in the selected municipalities was included to respond to the data collection instrument, which was applied online, totaling 322 units and, therefore, 322 professionals. The collected variables included information related to the work units, the respondents, as well as the care offered in terms of screening, monitoring, and case management. Data were tabulated using Excel spreadsheets and analyzed using SPSS® and JAMOVI® software. Results were summarized in frequencies, means, and standard deviations. Results: Of the 322 professionals sampled, 164 (50.9%) completed the study, with representation from all macro-regions of the state. The majority of respondents – 91.5% and 87.2%, respectively – reported carrying out screening actions for Systemic Arterial Hypertension and Diabetes Mellitus. However, the most common screening actions varied between the diseases. Active follow-up of absentees was the most frequently adopted monitoring practice, reported by more than 70% of respondents in both cases. Similarly, coordination with other points of care for individualized follow-up was the most commonly reported case-sharing strategy – 71.3% for hypertension and 70.7% for diabetes. A similar pattern of care was observed for both conditions. Final considerations: The results indicate that the state of Paraíba has implemented strategies for screening, monitoring, and care coordination for individuals with the analyzed chronic diseases. However, the low implementation rates of essential actions point to the need for ongoing training of professionals working in Primary Health Care, as well as the provision of adequate physical and organizational infrastructure to enable effective execution and, consequently, the consolidation of comprehensive and continuous care.